NATIVE LANGUAGE INFLUENCE ON THE PRODUCTION OF ENGLISH SENTENCE STRUCTURE - Endar Rachmawaty Linuwih (Edulitics (Education, Literature, and Linguistics) Journal, 2019)
Two main questions to be answered in this study are what the ill-formedness of English syntactic structures are made by the English Department students of Buddhi Dharma University, Tangerang and what the ill-formedness of English syntactic structures which get the influence of Bahasa Indonesia as their native language. A topic was given to be written in 3-5 paragraphs by 12 respondents who participated the study. The rules for constructing English syntactic structure were used to identify and determine the syntactically ill-formed sentences in English made by the respondents. The result obtained there are 3 groups of the ill-formedness of English syntactic structures; Noun Phrase, Verb Phrase, and Word Order, and 9 types of ill-formedness in constructing English syntactic structures. The types of the ill-formedness from the most frequent to the least frequent one are: Number, Agreement of Subject and Verb Form, Use of Prepositions, Use of Past Tense, Question sentence, Use of Verb, Use of the Verb Pattern, Embedded Question, Use of Present Tense, and. The ill-formed sentences appeared because of the interference of the students’ native language.